Analisis Enterprise Resource Planning (ERP) Terhadap Business Model Inovation (BMI) - Pontoh, Grace Theresia; Syamsuddin, Syamsuddin; Irwan, Rezkiyana Ulfha; Astari, Fitrah (JURNAL BISNIS STRATEGI, 2021)
This research was conducted at PT. Telekomunikasi Indonesia Tbk, which has a branch in Makassar with the aim of knowing how much influence Enterprise Resource Planning (ERP) has on Business Model Innovation (BMI). This study uses the interview method. Based on the research results, an ERP system helps automate various processes in a company both in automating customer management, financial management, and employee management. This ERP system software helps provide any information or data in realtime with a high degree of accuracy. The ERP system used by PT. Telekomunikasi Indonesia Tbk is a SAP R / 3 Enterprise.